Paediatric viral infections. - Lam, S.K. (1987)
Viral infections are probably the most important cause of childhood morbidity and mortality in the world. In many developing countries in South East Asia and the Western Pacific, priority health problems include acute respiratory infections, acute diarrhoeas and arboviral infections. Where studies have been carried out, there is no significant difference in the aetiological agents involved or in the manifestation of clinical childhood disease. Surveillance of these diseases have improved with the introduction of rapid viral diagnosis. The better understanding of the immunopathogenesis of many diseases have also encouraged research in this area and will lead to the better control and management of these diseases. However, the search for antivirals has been disappointing but fortunately new vaccines are on the horizon and the prospect for bringing some of these diseases under control through vaccination are bright.